Non-CpG methylation biases bisulphite PCR towards low or unmethylated mitochondrial DNA: recommendations for the field. Issue 1 (4th February 2020) - Morris, Margaret J; Hesson, Luke B; Youngson, Neil A
Abstract: Mitochondrial DNA (mtDNA) is a circular genome of 16 kb that is present in multiple copies in mitochondria. mtDNA codes for genes that contribute to mitochondrial structure and function. A long-standing question has asked whether mtDNA is epigenetically regulated similarly to the nuclear genome. Recently published data suggest that unlike the nuclear genome where CpG methylation is the norm, mtDNA is methylated predominantly at non-CpG cytosines. This raises important methodological considerations for future investigations. In particular, existing bisulphite PCR techniques may be unsuitable due to primers being biased towards amplification from unmethylated mtDNA. Here, we describe how this may have led to previous studies underestimating the level of mtDNA methylation and reiterate methodological strategies for its accurate assessment.